2023
DOI: 10.1039/d3cc02186f
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM1 produces stable, short, and cytotoxic Aβ40 protofibrils

Abstract: Monosialoganglioside GM1-bound amyloid β-peptides have been found in patients’ brains exhibiting early pathological changes of Alzheimer’s disease. Herein, we report the ability of non-micellar GM1 to modulate Aβ40 aggregation resulting...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This finding provides a new perspective and strategy for exploring the potential applications of GM1 in cellular functional regulation and the treatment of neurodegenerative diseases. [71][72][73][74] Further research can focus on investigating its impact on cell signal transduction and the regulatory mechanisms of related biological processes, thus gaining a deeper understanding of the functionality of GM1 within cells and its potential for disease treatment. This work has provided a detailed and insightful analysis of the behavior of cell membranes containing specific lipid components, which helps us to gain a deeper understanding of the structural and functional specificity of different lipid species.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides a new perspective and strategy for exploring the potential applications of GM1 in cellular functional regulation and the treatment of neurodegenerative diseases. [71][72][73][74] Further research can focus on investigating its impact on cell signal transduction and the regulatory mechanisms of related biological processes, thus gaining a deeper understanding of the functionality of GM1 within cells and its potential for disease treatment. This work has provided a detailed and insightful analysis of the behavior of cell membranes containing specific lipid components, which helps us to gain a deeper understanding of the structural and functional specificity of different lipid species.…”
Section: Discussionmentioning
confidence: 99%
“…Ahyayauch et al [ 18 ] showed that GM1 ganglioside was a major enhancer of Aβ binding to lipid bilayers in the L o state. In fact, gangliosides have repeatedly been described as promoting oligomer and fibril formation, in which their net negative charge is presumably involved [ 8 , 9 , 10 , 11 , 42 ]. The ganglioside effect may be non-linear with the dose.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the peptide was found either in the L d phase or at the boundary between ordered and disordered phases, in agreement with the data from Alvarez et al [ 6 ]. Several studies pointed out the facilitating role of GM1 ganglioside in Aβ oligomerization [ 8 , 9 , 10 , 11 ]. Cholesterol was also found to positively modulate Aβ oligomerization [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties of Aβ have been shown to be associated with the pathogenesis of Alzheimer’s disease (AD). Studies have reported the aggregation-induced oligomer formation and membrane-disrupting properties of Aβ peptides [ 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 ]. Studies have also reported the interaction between beta-amyloid and LL-37 peptides [ 205 ].…”
Section: Influence Of Ll-37 On Amyloid Aggregationmentioning
confidence: 99%